(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2021)
Abstract. In the current context export crediting, insurance and guarantee of export credits as state stimulation financial methods of export production have become an organic part of the states` foreign trade policy realization mechanism. Providing state guarantees for an export credit is in many cases a primary condition for obtaining it. Therefore, the importance of state insurance in foreign trade is constantly growing, which, in turn, increases the reliability and efficiency of export operations. Export credit agencies are a highly effective institutional mechanism of state promoting policy. The main advantages and disadvantages of export credit agencies are analyzed. Models of export financing are offered and the cost with the involvement of the export credit agency is indicated. Taking into account foreign experience, the main factors hindering the process of forming an effective system of state financial support for exports are identified and the feasibility of creating a specialized institution to support export activities in Ukraine is justified. After all, with the development of market relations and integration into the European economic space, characterized by the intensity of foreign trade, which is manifested in increasing the number and volume of export and import operations, there is a need to identify and study new economic mechanisms of financial support.